MEMBINA UKHUWAH ISLAMIYAH BERDASARKAN PETUNJUK ALQURAN - marhaban marhaban (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2019)
Muslim communities know the term ukhuwah Islamiyah. This term need to interpreted, so that our language does not experience confusion. For this reason, a linguistic review needed first to establish the position of the word Islamiyah in the above terms. During this time there was an impression the term mean